FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA HIPERTENSI DI POLIKLINIK INTERNA RSUP Prof. dr. R. D. KANDOU MANADO - Nonce Nova Legi (POLTEKKES KEMENKES MANADO, 2014)
Hypertension or high blood pressure is a condition where a person experiences anincrease in blood pressure above normal or chronic (a long time). Overweight(obesity), an inactive lifestyle (lazy exercise), stress, alcohol or salt in the diet; canlead to hypertension in people have lowered sensitivity. This study aimed todetermine the risk factors for hypertension in patients in the department of internalclinic Prof. dr. R. D. Kandou Manado.The study design was a case-control studies, in which the risk factors studiedretrospectively. The population in this study were all patients diagnosed withhypertension who visit the clinic of internal department of Prof. dr. R.D. KandouManado for cases and controls with an average visits in one month as many as 60people. While the sample in this study is the total population. Research carried outfor 1 month is the Moon in December 2013 in the internal clinic located in thedepartment of Prof. dr. R.D. Kandou Manado.The results showed a habit of meat consumption is not a risk factor for theoccurrence of hypertension in which the values of p> 0.05 (0.297). Likewise, thehabit of drinking alcohol is not a risk factor for hypertension in which the value of p>0.05 (0.301). However, obesity is a risk factor for the occurrence of hypertension inwhich the value of p <0.05 (0.001) which means that there is a significantassociation between obesity and hypertension. Based on the results of the study itcan be concluded that : Freedom of meat and alcohol consumption is not a riskfactor for hypertension, while obesity is a risk factor for hypertension in patients inthe clinic internal department of Prof. dr. R.D. Kandou Manado. It is recommendedfor patients to pay attention to the ideal weight and is expected to further researchexamining other risk factors of hypertension.